Prevalence of Subclinical Mastitis and Associated Bacterial Pathogens in Milkshed Districts of Odisha, India - Sarangi, Swetapadma; Sahoo, Niranjana; Biswal, Sangram; Pahari, Avishek; Sardar, Kautuk K.; Das, Bhabesh C. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study deals with subclinical mastitis (SCM) with respect to prevalence, etiology and antibiogram pattern. A total of 1273 cross-bred Jersey lactating cows in four milkshed districts of Odisha viz. Jagatsinghpur, Puri, Khordha and Cuttack were screened through modified california mastitis test during the period from September 2019 to January 2020. Overall 57.58% prevalence of SCM was recorded. Microbiological examination of 72 milk samples positive for SCM revealed association of Staphylococcus aureus in maximum (65.27%) cases followed by Streptococcus uberis (9.7%), Streptococcus agalactiae (8.3%), Pseudomonas aeruginosa (5.55%) and Escherichia coli (2.76%). In vitro antibiotic sensitivity test results indicated > 95 % S. aureus isolates were quite sensitive to the antibiotics like gentamicin, ceftizoxime, cefuroxime and ceftiofur.